2010
DOI: 10.1038/hr.2010.81
|View full text |Cite
|
Sign up to set email alerts
|

Medical expenditures of men with hypertension and/or a smoking habit: a 10-year follow-up study of National Health Insurance in Shiga, Japan

Abstract: Hypertension and smoking are major causes of disability and death, especially in the Asia-Pacific region, where there is a high prevalence of a combination of these two risk factors. We attempted to measure the medical expenditures of a Japanese male population with hypertension and/or a smoking habit over a 10-year period of follow-up. A cohort study was conducted that investigated the medical expenditures due to a smoking habit and/or hypertension during the decade of the 1990s using existing data on physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In Japan, where the rate of smoking in males exceeds that of males in developed Western countries [4], [5], 38.6% of cancer-related deaths, 23.4% of deaths due to respiratory tract disease, and 23.0% of deaths due to cardiovascular disease among Japanese males have been attributed to a history of smoking [2]. Smoking is burdensome because of the effects on premature disability and excess mortality [2], [3] and also because of the substantial costs to medical insurers in Japan [6], [7]. Izumi et al [6] showed that over a follow-up period of 30 months, Japanese males with a history of smoking incurred medical costs averaging ¥3,000 per month in excess of the costs attributed to individuals who had never smoked.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, where the rate of smoking in males exceeds that of males in developed Western countries [4], [5], 38.6% of cancer-related deaths, 23.4% of deaths due to respiratory tract disease, and 23.0% of deaths due to cardiovascular disease among Japanese males have been attributed to a history of smoking [2]. Smoking is burdensome because of the effects on premature disability and excess mortality [2], [3] and also because of the substantial costs to medical insurers in Japan [6], [7]. Izumi et al [6] showed that over a follow-up period of 30 months, Japanese males with a history of smoking incurred medical costs averaging ¥3,000 per month in excess of the costs attributed to individuals who had never smoked.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison was made because of the fact that a very small percent- Analysis of covariance was used to compare logtransformed monthly medical expenditure in each blood pressure category, after adjustment for age, body mass index, drinking habit, serum total cholesterol, and a history of diabetes. From Nakamura et al [8] .…”
Section: Other Relevant Topicsmentioning
confidence: 99%
“…Although we manually searched for extra relevant articles in the reference lists of the identified articles and other publications, no additional relevant article was identified from these sources. Of the six relevant articles, three articles were from the same cohort study, but each dealt with different topics without duplicate publication [6][7][8] . The remaining three articles were all different [9][10][11] .…”
Section: Search Strategy and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Japanese male population, hypertensive individuals with a smoking habit were reported to incur higher medical expenditures than individuals with a smoking habit alone, hypertension alone, or neither. 5 Over 50 years ago, lung cancer was reported to be caused by smoking, and since then, many diseases have been reported to be caused by smoking and involuntary exposure to cigarette smoke. In particular, chronic kidney disease is a growing worldwide problem that has increasingly been shown to be interwoven with CVD and smoking.…”
mentioning
confidence: 99%